Reliability and equivalence of alternate forms for the Symbol Digit Modalities Test: implications for multiple sclerosis clinical trials - Benedict, Ralph HB; Smerbeck, Audrey; Parikh, Rajavi; Rodgers, Jonathan; Cadavid, Diego; Erlanger, David (Multiple sclerosis, 2012)
Background: Cognitive impairment is common in multiple sclerosis (MS), but is seldom assessed in clinical trials investigating the effects of disease-modifying therapies. The Symbol Digit Modalities Test (SDMT) is a particularly promising tool due to its sensitivity and robust correlation with brain magnetic resonance imaging (MRI) and vocational disability. Unfortunately, there are no validated alternate SDMT forms, which are needed to mitigate practice effects. Objective: The aim of the study was to assess the reliability and equivalence of SDMT alternate forms. Methods: Twenty-five healthy participants completed each of five alternate versions of the SDMT – the standard form, two versions from the Rao Brief Repeatable Battery, and two forms specifically designed for this study. Order effects were controlled using a Latin-square research design. Results: All five versions of the SDMT produced mean values within 3 raw score points of one another. Three forms were very consistent, and not different by conservative statistical tests. The SDMT test–retest reliability using these forms was good to excellent, with all r values exceeding 0.80. Conclusions: For the first time, we find good evidence that at least three alternate versions of the SDMT are of equivalent difficulty in healthy adults. The forms are reliable, and can be implemented in clinical trials emphasizing cognitive outcomes.